Religious persecution and political order in the United States - Smith, David T. (Cambridge studies in social theory, religion, and politics, 2015)
Religious freedom and persecution in America: a theoretical overview -- Joseph Smith and the rise of Mormonism -- The federal response to Mormonism -- Jehovah's Witnesses and the flag salute, 1870-1940 -- Mass violence against Jehovah's Witnesses, 1940-1942 -- The Catholic experience in America -- The Jewish experience in America -- The Islamic experience in America